The Design of IoT Water Control System - Muhammad, Zulkiflee; Osman, Mashanum; Razali, Sazalinsyah (Journal of Advanced Computing Technology and Application (JACTA), 2020)
Wastage of water is a bad practice for every human being on earth. The features of the water wastage feature can be divided into several types. Examples of the types are wastage at home, domestic wastage and wastage from the industry. In this study, domestic wastage is a priority because the problem was contributed to a reduction of water percentage in the watershed, whether at home or at the water plant. This should be resolved in the right way to avoid it occurring continuously. In this case, one way to take is to build an application called the Water Control System. This application is capable of detecting open pipes due to negligence or certain reasons. The purpose of this study is to give the easier solution to solve the wastage of water problem and provide information about how to solving it. This system will give benefit not only to domestic user or household, but also toward the industry that use a lot of water for their daily requirement. Hope that this study will help a lot by identify the problem and provide for the solution to user.